Effects of Six Natural Extracts on the Color, Oxidative Stability and Flavor Characteristics of Oil-Fried Shiitake Mushroom - CHEN Dong, WANG Ruixue, WANG Hongli, KONG Qinglong, XU Xiaohan, LIN Songyi (Shipin Kexue)
In this study, the effects of the extracts from mulberry leaves, rosemary, cinnamon, grape seeds, green apples and cloves on the color, oxidative stability and flavor characteristics of oil-fried shiitake mushroom were investigated. It was found that these natural extracts improved the brightness of oil-fried shiitake mushroom and significantly inhibited its browning. The content of melanoid, the Maillard reaction product, was decreased by treatment with each of the extracts, which shared a similar trend with the change in the degree of browning. The natural extracts also significantly improved the antioxidant capacity and inhibited the oxidation reaction of oil-fried shiitake mushroom. Clove extract resulted in the largest decrease in peroxide value (74.36%), while green apple extract resulted in the greatest decrease in thiobarbituric acid reactive substances (TBARS) value (17.54%). Clove, rosemary and grape seed extracts significantly inhibited protein oxidation. Treatment with green apple extract minimized the free radical content. The umami and saltiness were significantly increased by treatment with clove, rosemary or mulberry leaf extract. All six natural extracts increased the levels of nitrogen and oxygen compounds, hydrocarbons, alcohols, aldehydes, and ketone. Seventeen differential volatile compounds, such as methyl 2-methoxybenzoate and isoamyl 2-methylbutyrate, were identified among the six treatment groups and the control group. These results provide a theoretical basis for the application of natural extracts in oil-fried edible mushrooms.